Partial compliance with long-acting paliperidone palmitate and impact on hospitalization: a 6-year mirror-image study - Sofia Pappa; Katy Mason (SAGE Publishing, 2020)
Background: Previous studies showed a linear correlation between partial compliance with an oral antipsychotic medication and hospitalisation risk among patients with schizophrenia. Long-acting injections (LAIs) may significantly improve adherence and reduce relapse in patients with psychosis. The aim of this study was to evaluate the relationship between the level of compliance with 1-monthly paliperidone palmitate (PP1M) and hospitalisation rates. Methods: This was a naturalistic, mirror-image study examining retention, compliance and hospitalisation rates 3 years pre- and 3 years post-PP1M initiation. Compliance was divided in three groups: full (no missed dose/year), good (6-11injections/year), poor (<6 injections/year). Results: A total of 173 patients suffering from a severe mental illness (70% with a diagnosis of schizophrenia and 30% with other diagnoses) were included; 77% of patients continued PP1M for 1 year, 66% for 2 years and 55% for 3 years. Of the 95 patients who remained on PP1 throughout the 3 years of follow up, 81% showed full, 13% good, and only 6% poor compliance. In the patients who were fully compliant, the mean number of hospital admissions decreased from 1.34 to 0.43, and the mean number of bed days from 82 to 19 days per patient 3 years before and 3 years after PP1M initiation ( p  < 0.001). It is noteworthy that the reductions in hospital stay were statistically significant for the group of patients with full compliance but not for the other two groups. In fact, patients with poor compliance demonstrated higher hospitalisation rates both before and after PPM1 initiation. These findings were similar in the subgroup of patients with schizophrenia who continued treatment for 3 years ( n  = 68). Conclusion: There was a direct association between partial compliance and re-hospitalisation; fully compliant patients maintained the best outcomes in terms of reduced bed use following PPM1 initiation.